Mnangagwa's Zimbabwe: Crisis? What Crisis?. (March 2021) - Helliker, Kirk; Chikozho Mazarire, Gerald
Three years after the November 2017 coup in Zimbabwe and the installation of Emmerson Mnangagwa as ruling party and state president, there is growing scholarly interest in identifying the character of the post-coup regime, particularly in comparison to the 37-year reign of Robert Mugabe's ZANU-PF. So far, there are continuities and changes, with increasing concerns about a qualitative shift in the militarization of Zimbabwean state and society under Mnangagwa and the further closing down of civil society space. Perhaps more so than during the first two years of post-coup Zimbabwe, this has become abundantly clear during the Covid-19 pandemic lockdown.